MECP2-related disorders while gene-based therapies are on the horizon - Allison, Katherine; Maletic-Savatic, Mirjana; Pehlivan, Davut (Frontiers in Genetics, 2024)
The emergence of new genetic tools has led to the discovery of the genetic bases of many intellectual and developmental disabilities. This creates exciting opportunities for research and treatment development, and a few genetic disorders (e.g. spinal muscular atrophy) have recently been treated with gene-based therapies. MECP2 is found on the X chromosome and regulates the transcription of thousands of genes. Loss of MECP2 gene product leads to Rett Syndrome, a disease found primarily in females, and is characterized by developmental regression, motor dysfunction, midline hand stereotypies, autonomic nervous system dysfunction, epilepsy, scoliosis, and autistic-like behavior. Duplication of MECP2 causes MECP2 Duplication Syndrome (MDS). MDS is found mostly in males and presents with developmental delay, hypotonia, autistic features, refractory epilepsy, and recurrent respiratory infections. While these two disorders share several characteristics, their differences (e.g. affected sex, age of onset, genotype/phenotype correlations) are important to distinguish in the light of gene-based therapy because they require opposite solutions. This review explores the clinical features of both disorders and highlights these important clinical differences.